Analysis on the variation rule and influencing factors of energy consumption carbon emission intensity in China's urbanization construction. (20th November 2019) - Han, Xiuyan; Cao, Tianyi; Sun, Tao
Abstract: On the basis of literature review and current situation analysis, models were established to carryout scientific measurement for carbon emissions and its intensity in China in this paper. With full consideration to the actual situation of energy consumption growth and carbon emission intensity controlling of energy consumption in new-type urbanization construction, the Kaya model was revised. With population intensity of GDP production, urbanization rate, employment rate of urban population, per capita energy consumption of urban employed population and carbon emission density of energy consumption selected as independent variables, test models of multivariate linear correlation were established for new-type urbanization construction, energy consumption growth and carbon emission intensity controlling of energy consumption, and the empirical equilibrium equation and error correction equation were determined through stability test, lag order test and co-integration test. The results are shown as follows: the urban employment rate (UER) has the greatest impact on carbon emission intensity, the per capita urban employment energy consumption (PEC) has the least impact on carbon emission intensity, and the degree of other factors in proper order is: urbanization rate (UR), population intensity of GDP production (PG) and carbon emission density (CD). Graphical abstract: Image 10106 Highlights: Energy consumption is the main source of China's carbon emissions and environmental pollution. China's urbanization has contributed to the reduction of energy consumption and carbon emission intensity. The change law of energy consumption carbon emission intensity in China's urbanization construction is analyzed. Kaya model was adopted to study the influencing factors of carbon emission intensity control.